The Concept of Syafaat (Intercession) in Education: A Study of the Book Nurul Mubin - Brilian, Khoiruman Ahmad; Sopingi, Imam; Hidayati, Athi’ (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Incorporating spiritual values into Islamic education is considered essential for creating a more humane, just, and character-building system. This research aims to examine the concept of Syafaat (Intercession) from an Islamic educational perspective by analyzing the kitab Nurul Mubin. The book is a classical work that elaborates on the meaning and forms of intercession within religious and social contexts. A qualitative approach with a literature review method is used to explore the ideas contained in the text, especially those related to the values of intercession as expressions of compassion, help, and second chances. The findings indicate that intercession is not only relevant in eschatological (akhirat) contexts but also has significant implications in the world of education, such as the important role of teachers as academic intercessors, the application of empathy in student development, and providing opportunities for correction for students who experience learning setbacks. Therefore, the concept of Syafaat (Intercession) can be used as a humanistic approach within the Islamic education system, emphasizing justice, compassion, and character development. This research is expected to inspire the development of an Islamic educational system that incorporates spiritual values and justice.